Dr. Kiranmoy Sarangi — Deep Plane Facelift - Sarangi, Kiranmoy (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Kiranmoy Sarangi, India. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003143; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; india